Enhancing Public Financial Management through Performance Evaluation and Cost Systems - Nurfadila, Nurfadila (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study aims to explore public financial management (PFM) through performance evaluation and cost systems, seeking to enhance the efficiency, effectiveness, and accountability of managing public funds. The study highlights the importance of integrating performance evaluation and cost systems to achieve optimal resource allocation and transparency in attaining societal objectives. Research Design and Methodology: This research employs a qualitative approach through a literature review. The research process involves systematic searches of relevant literature, thematic analysis, and synthesis of findings from various studies. The focus is on the design, implementation, and impact of performance evaluation and cost systems in PFM and the challenges and opportunities encountered in their application. Findings and Discussion: The findings indicate that integrating performance evaluation and cost systems can improve public financial management by providing more comprehensive information for decision-making. This integration enables governments to allocate resources more efficiently, identify areas for improvement, and enhance transparency and accountability in managing public funds. However, the study also identifies challenges related to data availability, organizational complexity, and cultural resistance to change. Implications: This study has a practical impact on governments and policymakers in optimizing public financial management. Investment in data infrastructure, capacity-building, and change management strategies is necessary to overcome challenges in implementing integrated performance evaluation and cost systems. Furthermore, the study encourages further research to explore these integrated systems' long-term impact and sustainability in different contexts.